The Balkans: From balance of power to balance of human welfare - Bašić Nedžad (Međunarodni Problemi, 2005)
The principles of territorial integrity and (non)interference halt the influence of self-determination. Legal relationship between these principles become much more complex in the Balkans despite the strong regard given to preserving the territorial integrity of the state. One of the repercussion of this controversial relationship is that human right stay without effectual protection in the case of conflict between these two principles. In this circumstance central government and movement to self-determination are supported to settle its claims by restoring to armed hostilities. The author explains how international community can reduce the inherent conflict as the working out of these principles in light of the forces of democratisation and respect for human rights, peace and development comes to make the parties see them as less and less irreconcilable.